2005
DOI: 10.1002/chin.200512221
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Thymidylate Synthase Inhibition by Trifluorothymidine in FM3A Cells

Abstract: For Abstract see ChemInform Abstract in Full Text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 1 publication
1
7
0
Order By: Relevance
“…TS inhibition is a major mechanism of action of classical fluoropyrimidines such as 5‐FU (Van Triest and Peters, ). Although TS inhibition by FTD‐MP may partly account for the antitumor effects of FTD (Santi and Sakai, ; Temmink et al ., ), the incorporation of FTD‐TP into DNA and the resulting DNA damage appear to be the major mechanism of action of FTD (Tanaka et al ., ; Suzuki et al ., ; Matsuoka et al ., ). Importantly, TAS‐102 exhibits antitumor activity against FU‐resistant cell lines in preclinical xenograft models (Emura et al ., ; Emura et al ., ; van der Velden et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…TS inhibition is a major mechanism of action of classical fluoropyrimidines such as 5‐FU (Van Triest and Peters, ). Although TS inhibition by FTD‐MP may partly account for the antitumor effects of FTD (Santi and Sakai, ; Temmink et al ., ), the incorporation of FTD‐TP into DNA and the resulting DNA damage appear to be the major mechanism of action of FTD (Tanaka et al ., ; Suzuki et al ., ; Matsuoka et al ., ). Importantly, TAS‐102 exhibits antitumor activity against FU‐resistant cell lines in preclinical xenograft models (Emura et al ., ; Emura et al ., ; van der Velden et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…FTD-resistant H630 colon cancer cells through intermittent exposure of FTD also decreased TK protein expression and activity, but FTD-resistant H630 cells through continuous exposure of FTD decreased hENT and increased secretory phospholipase-A2 (sPLA2) gene expression (4). A different approach using random mutagenesis and drug selection showed that loss of TK or TS activity in the mouse mammary carcinoma cell line FM3A is associated with severe FTD resistance (11). On the other hand, FTD-resistant DLD1 cells established by Tsunekuni and colleagues overexpress the miRNA let-7d-5p, which may be the cause of FTD resistance (14).…”
Section: Introductionmentioning
confidence: 99%
“…Trifluridine exerts its cytotoxicity after transformation by thymidine kinase to trifluoromethyl deoxyuridine 5ʹ-monophosphate (F 3 dTMP) followed by conversion to F3dTTP, which is then incorporated into DNA, causing DNA single strand breaks along with a degree of TS inhibition. When trifluridine was administered as a twice daily dose in mouse models, there was greater DNA incorporation, whereas a continuous infusion resulted in greater TS inhibition [38,39].…”
Section: Oral Formulationsmentioning
confidence: 97%